2014
DOI: 10.1002/ijc.28845
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence that secretion of HLA‐G by immunogenic tumor cells allows their evasion from immunosurveillance

Abstract: Human leukocyte antigen‐G (HLA‐G) expression by tumors has been evidenced in numerous malignancies in association with poor prognosis and resistance to immunotherapy in humans. Particularly, soluble form of HLA‐G was measured at high concentrations in malignant effusions and plasma from cancer patients, and inhibits antitumor immune cells in vitro through interaction with immunoglobulin‐like transcript (ILT) receptors. Nevertheless, in vivo study demonstrating that HLA‐G secretion by tumor cells allows their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 50 publications
(118 reference statements)
3
45
0
1
Order By: Relevance
“…HLA-G can directly inhibit immune cell function through receptor binding and/or through trogocytosis and impairment of chemotaxis (15,16); moreover, HLA-G can render tumor cells with a higher invasive, metastatic potential and an unfavorable prognosis in tumor patients, indicating that HLA-G expression has multiple effects including promoting tumor cells to escape immune surveillance and enhancing their metastasis during the progression of malignancies (17)(18)(19). Therefore, the role of HLA-G in malignancies has gained considerable clinical interest for the possibility of exploiting it as a molecular biomarker and a therapeutic target.…”
mentioning
confidence: 99%
“…HLA-G can directly inhibit immune cell function through receptor binding and/or through trogocytosis and impairment of chemotaxis (15,16); moreover, HLA-G can render tumor cells with a higher invasive, metastatic potential and an unfavorable prognosis in tumor patients, indicating that HLA-G expression has multiple effects including promoting tumor cells to escape immune surveillance and enhancing their metastasis during the progression of malignancies (17)(18)(19). Therefore, the role of HLA-G in malignancies has gained considerable clinical interest for the possibility of exploiting it as a molecular biomarker and a therapeutic target.…”
mentioning
confidence: 99%
“…In the context of MDSCs, interaction between HLA-G and murine cell receptor PIR-B (homology with the human ILTs) could expand the population of CD11 b+ Gr 1+ PIR-B+ or CD11b + Ly6G + MDSCs, which could decrease NK cytotoxic activity [19,20]. Moreover, in ILT-2 transgenic mice, HLA-G has been found to induce the emergence of CD11b + Gr1 + MDSCs with an enhanced suppressive activity and directly involved in the prolongation of allogeneic skin graft survival [34].…”
Section: Discussionmentioning
confidence: 99%
“…The murine receptor paired immunoglobulin like receptor-B (PIR-B), a homology to human ILTs, can bind to HLA-G [18]. Previous findings had recognized that through binding to the PIR-B expressed on MDSCs, and HLA-G has been found with the capability to contribute the expansion and suppressive functions of MDSCs [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that interaction between HLA-G and PIR-B could expand the population of CD11b + Gr1 + PIR-B + MDSCs in an immunocompetent HLA-G1 + M8 (a human melanoma cell line) tumor-bearing mouse model, which could decrease NK cytotoxic activity [5]. In another study, in a mouse model with murine mammary 4T1 cell line, HLA-G5 was observed to favor the CD11b + Ly6G + mice G-MDSC expansion with binding to PIR-B [19]. Moreover, in ILT-2 transgenic mice, HLA-G has been found to induce the emergence of CD11b + Gr1 + MDSCs with an enhanced suppressive activity and directly involved in the prolongation of allogeneic skin graft survival [20].…”
Section: Editorialmentioning
confidence: 93%